A case of pulmonary Mycobacterium avium infection in an immunocompetent patient who showed a huge consolidation with a high FDG uptake on PET/CT. (2016) - Kato, Akane; Yamamoto, Hiroshi; Ikeda, Mariko; Tateishi, Kazunari; Ushiki, Atsuhito; Yasuo, Masanori; Kawakami, Satoshi; Asaka, Shiho; Oguchi, Kazuhiro; Hanaoka, Masayuki
Abstract: We encountered a middle-aged afebrile immunocompetent woman with a slight cough. Positron emission tomography (PET)/computed tomography (CT) revealed a broad left upper-lobe consolidation without cavity lesions, small nodules, or bronchiectasis showing a positive fluorodeoxyglucose (FDG) uptake with a maximum standardized uptake value (SUVmax) of 26.9. Percutaneous needle lung biopsy specimens showed caseous granulomas without atypical cells and Mycobacterium avium was cultured from left pleural effusion, which developed after the biopsy. The consolidation significantly decreased following combination chemotherapy for approximately 2 years. Clinicians should remember that pulmonary M. avium infection could result in a large consolidation without other typical radiological findings.